Organic Growth Marketing Strategies in Hospitality Industry - Ivasciuc, Ioana Simona (International Journal of Economic Practices and Theories, 2014)
Hospitality industry is the world’s fastest growing industry accountable of earning incredible profits in the international market. Though each region and nation faces its own challenges and can take advantage of particular opportunities, certain basic operating principles will allow the international hospitality industry to expand and prosper regardless of specific location. In order to fulfil a strategic direction a hospitality business will need to consider various strategic methods. This may include the formation of an alliance and merger with, or the acquisition of another organization. Alternatively the organization may decide to achieve its selected strategy alone by growing organically. Organic growth represents the true growth for the core of the company. Achieving sustainable and profitable organic growth requires more than new ideas, innovation, and strong execution. Rather, organic growth exemplars embed a set of institutional capabilities and a growth culture that define the organization and that are key enablers to realizing advantaged performance. In order to understand how hotel managers in Romania use organic growth principles in their organizations and how they overcome the growth barriers, a qualitative research was used to collect data from a sample of hotel managers. The central themes they were question about are: organizational structures and processes, role of people and leadership in their organization, reasons for growing, best ways for growing, measuring instruments for growing, risks of growing and what marketing strategies do they use to manage those risks.